Effects of Silica-NPK Mixed Fertilizer Application on Milling Quality of Malaysian Rice - Chong Patcharida (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To synthesise and analyze silica from rice husk ash (RHA). To prepare and characterize silica-NPK mixed fertilizer. To evaluate the effect of silica-NPK mixed fertilizer application at various silica concentrations on the milling quality of rice.